Photoelectrochemical characterisation of direct and pulse electrodeposited copper on fluorine-doped tin oxide glass / Nur Azlina Adris ... [et al.] - Adris, Nur Azlina; Jeffery Minggu, Lorna; Mohamad Yunus, Rozan; Arifin, Khuzaimah; Mohamed, Mohamad Azuwa; Kassim, Mohammad (Universiti Teknologi MARA, 2024)
Electrodeposition (ED) is applied in several applications since it is one of the most user‐friendly and cost-effective techniques. The increasing popularity of this technique is due to its capacity to control the morphology and chemical composition of the target materials. Copper (Cu) is one of the metals that can be discovered in the greatest abundance on earth. It has been used as an alternative to noble metals to improve the photo electrochemical (PEC) activity for hydrogen generation. This research involved the electrochemical deposition of Cu metal onto fluorine-doped tin oxide (FTO) glass using direct and pulse ED. The objective of this study is to investigate the PEC performance of Cu metal electrodeposited on FTO glass by evaluating its efficiency under light illumination. The deposition of the Cu films was successful, resulting in a thin layer of Cu films onto the FTO. The PEC response of metallic Cu was analysed by doing an LSV study on the thin films, in relation to the ED technique, applied voltage, ED time, and pulse cycle. The results show that the FTO/Cu −0.8 V samples produced via pulse ED have the highest PEC activity. The deposition of strongly adhering and improved morphology of Cu thin film is important especially for interconnect in semiconductor applications.